Characterization Of Hydrogenation Behavior Of NaAlH4 Utilizing Thermoelectric Power And Magnetic Analyses - A. N. Lasseigne (The Minerals, Metals and Materials Society, 2006)
Hydrogenation behavior of the NaAlH4 intermetallics is investigated utilizing thermoelectric power and magnetic analyses. Using both thermoelectric power and magnetic susceptibility measurements on these intermetallics allows for confirmation and further insight into hydrogen's role in altering the material's electronic structure. The electronic and magnetic property correlations will indicate the direction for further alloy development to optimize hydrogen storage.